An open-label study to assess the effect of a single dose of Nebivolol and Ivabradine on heart rate and pulse wave velocity in hypertensive patients receiving amlodipine - Pathapati, Rama Mohan; Reddy, Chirra Bakthavasthala; Buchineni, Madhavulu; Sujith, Tumkur Rajasekhar; Kumar, Meriga Rajesh; Kolla, Praveen (International Journal of Basic & Clinical Pharmacology, 2017)
Background:Increased resting heart rate (HR) has emerged as an independent risk factor in the general population and in patients with hypertension, coronary artery disease, and myocardial infarction. HR is strongly and directly associated with arterial rigidity in hypertensive patients. Nebivolol (N) and Ivabradine (I) were established HR lowering agents. In this study, we have evaluated Nebivolol and Ivabradine on HR and pulse wave velocity in hypertensive patients who were receiving Amlodipine. Methods: A total of 18 hypertensive patients on Amlodipine participated in our study. Nine received Nebivolol and others received Ivabradine. We measured HR, blood pressures (BPs) and carotid-femoral pulse wave velocity (cf PWV - an index of large artery stiffness) non-invasively at baseline and 2 hrs after administration of single oral dose of 5 mg N and 5 mg of I. Results: The mean change in HR (−21.7±7.1 vs. −13.89±7.4 beats/min p=0.03) and cf PWV (−0.27±0.58 vs. −2.31±2.1 m/s p=0.01) was statistically significant after treatment in N and I groups respectively. However, there was no significant change in systolic BP (−17.3±9.1 vs. −15.1±11.1 mmHg p=0.65) and diastolic BP (−3.5±5.0 vs. −8.0±6.4 mmHg p=0.11) after treatment in N and I groups, respectively. Conclusions: Nebivolol is an effective HR lowering agent compared to Ivabradine. However, significant decrease in arterial stiffness was observed with Ivabradine.